Prevalencia de las patologías musculoesqueléticas en los fisioterapeutas. - Montesdeoca Vaca, Diana Mishell (2024)
This research work consists of a compilation and bibliographic review of scientific articles obtained from various search engines such as PubMed, Google Scholar, Elsevier, and Redalyc, with the aim of analyzing the prevalence of musculoskeletal disorders in physiotherapists through an exhaustive search of high-impact articles, rigorously selected following inclusion and exclusion criteria. The methodology used is documentary, with an inductive approach, descriptive level, and a qualitative focus. The prevalence of musculoskeletal disorders in physiotherapists is high due to the physical nature of their work, with frequent pain in the neck, upper back, and lower back. These conditions affect their quality of life and work performance. It is essential to implement preventive strategies, such as ergonomic education, to reduce the incidence of these disorders and improve their well-being. Currently, the prevalence of musculoskeletal disorders in physiotherapists remains a significant concern in the health field. As these professionals continue to provide care to patients with various conditions, they face a high risk of developing disorders related to physical overload and repetitive stress. Long working hours, uncomfortable postures during treatment sessions, and handling patients with varied needs contribute to this problem. Additionally, the lack of awareness about the importance of self-care and prevention in the profession can exacerbate the situation. It is crucial to implement ergonomic measures, exercise programs, and training in proper body handling techniques to reduce the incidence of injuries among physiotherapists and promote their long-term well-being.